Biodegradable Nanomaterials in Drug Delivery Systems: Review Article (Journal of Pharma Insights and Research, 2025)
Biodegradable nanoparticles have revolutionized drug delivery by enhancing therapeutic efficacy while minimizing environmental impact. These nanocarriers, composed of biocompatible polymers, lipids, proteins, and inorganic materials, enable targeted drug delivery and controlled release kinetics, reducing dosing frequency and improving patient compliance. Their natural degradation into non-toxic byproducts addresses long-term toxicity concerns and offers an environmentally conscious alternative to conventional delivery systems. Polymeric nanoparticles, particularly those based on chitosan, polylactic acid (PLA), and poly(lactic-co-glycolic acid) (PLGA), demonstrate remarkable versatility in drug encapsulation and release profiles. Lipid-based carriers like liposomes and solid lipid nanoparticles effectively transport both hydrophilic and hydrophobic drugs. Protein-based and inorganic biodegradable nanocarriers further expand the scope of sustainable drug delivery, especially in targeted therapies. Recent advances include the development of smart, stimuli-responsive nanomaterials that release drugs in response to specific environmental triggers such as pH, temperature, or enzymatic activity. While these systems show tremendous potential, challenges in scalability, stability, and regulatory compliance need resolution for widespread clinical implementation. Green synthesis methods are emerging to enhance production sustainability and reduce environmental impact.